Financial, equipment and sanitation aspects of hospital food services in the Philippines - De los Santos, Estrella Bernabe 1948-; Florencio, Cecilia A. (1979)
This study was part of the University of the Philippines- National Science Development Board research project entitled "A Comprehensive Study of the Delivery of Nutritional Services in Hospitals in the Philippines". The primary objective of this phase of the research was to describe and assess the financial, equipment, and sanitation aspects of hospital food services in the Philippines. Data were gathered through the use of questionnaires, interviews, and by actual observations. Seventy two (72) hospitals representing approximately ten percent (10%) of the total population in Luzon and Visayas, constituted the sample. Three research teams gathered the data simultaneously in the different regions. Findings indicated that the average daily per capita food costs varied considerably and were related to differences in regional location, type of hospital ownership, hospital size, and presence of a nutritionist/dietitian. Majority of the dietary departments had inadequate records of food service costs. Cost control practices in all areas of food service management were also generally "poor". Majority of the respondents had inadequate equipment and facilities. Visual inspections of the dietary departments showed that majority had poor sanitation, i.e. unsatisfactory housekeeping and garbage disposal system, inadequate rodent and insect control program, lack of toilets and washroom facilities, poor dishwashing procedures and unsatisfactory personal hygiene of dietary workers. The Chi-square tests indicted that the usage of cost control records related significantly to the presence of nutritionist/dietitian but not to the type of hospital ownership and bed size. Analysis of variance revealed that sanitation scores were not significantly related to type of ownership, bed size, and presence of nutritionist/dietitian.
Appendices: leaves 175-271.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Vita.
Keywords: Hospitals -- Philippines -- Food service